Effect of Superchilling on Preservation, Ripening and Senescence of Broad Bean Seeds - LI Die, LI Haiyan, ZHONG Shihong, FU Yuansheng, LI Meiqing, ZHANG Haiwei (Shipin Kexue)
This study sought to investigate the effect of superchilling on the preservation of fresh broad bean seeds. Three superchilling temperatures (−2, −3 and −4 ℃) were determined based on the freezing point of broad bean seeds. The effects of superchilling storage at each temperature on the sensory quality, chlorophyll content, color difference values and other quality indexes of broad bean seeds were analyzed using chilled storage (4 ℃) as a control, and then the effects of superchilling storage on the ripening and senescence of broad bean seeds were studied by determining the activities of polyphenol oxidase (PPO), peroxidase (POD) and phenylalamine ammonia lyase (PAL), total phenol content, soluble protein content and the cell structure. The results showed that the shelf life of broad bean seeds stored at 4 ℃ was 7 d, and all three superchilling temperatures significantly improved the sensory quality of the samples. Superchilling at −3 ℃ kept broad bean seeds fresh for up to 35 d, significantly slowing down the decrease in chlorophyll content and the increase in mass loss rate and color difference values during storage and maintaining the hardness well. Principal component analysis (PCA) showed that the optimal superchilling temperature was −3 ℃. Superchilling storage at −3 ℃ slowed down the elevation of PPO and PAL activities, maintained a higher POD activity, and delayed the generation of starch and soluble protein as well as the accumulation and the rate of change of total phenol content in broad bean seeds. Moreover, it maintained the relative stability of the cell structure and morphology and delayed the ripening and senescence of broad bean seeds.